Educação hospitalar: o papel do pedagogo - Joia, Taynara Nathália Casarin [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Pedagogy is understood as a range that empowers the pedagogue for various branches; one of them is Hospital Pedagogy. This study had as objective to present this specialty and to analyze about the pedagogical performance in this area; introducing initially to the research the historical approach on how this class came about and why it becomes so essential to its inclusion in hospitals. The hospital class emerged in the 1930s after the Second World War and since then has been expanding more and more within the hospitals where children and adolescents of school age are found, in order to reduce the distance between the internees and the school, thus avoiding that, due to long-term hospitalization circumstances, they may be kept out of school for repetition and / or avoidance. Thus, the hospital pedagogy, conciliates the treatment and the schooling process. According to a survey conducted in 2015, there are currently 141 hospitals in Brazil that offer the opportunity for children and young people to continue their studies. This survey will address 3 of these hospital-grade hospitals. The roles of the pedagogue will be analyzed and how this process was and is inserted in the reality of children and adolescents hospitalized. The study was carried out within a qualitative bibliographic approach, and supported by several researchers, emphasizing the importance of communication in the schooling process and how the health network can and should host the school in its places of hospitalization, so that the child and adolescent, feel more welcomed, and without the loss of academic knowledge, and with this, the hospital, becomes more humanized

Entende-se a Pedagogia como um leque que capacita o pedagogo para vários ramos; um deles é a Pedagogia Hospitalar. Este estudo teve como objetivo apresentar essa especialidade e analisar sobre a atuação do pedagogo nesta área; introduzindo inicialmente à pesquisa a abordagem histórica sobre como surgiu esta classe e o porquê se faz tão imprescindível à inclusão da mesma nos hospitais. A classe hospitalar surgiu na década de 30, após a segunda guerra mundial e desde então, vem se expandindo cada vez mais dentro dos hospitais no qual se encontram crianças e adolescentes em idade escolar, com o objetivo de diminuir a distância entre os internados e a escola, evitando assim, que por circunstâncias de internação em longo prazo, fiquem afastadas da escola, para ao haver repetência e/ou evasão. Assim, a pedagogia hospitalar, concilia o tratamento e o processo de escolaridade. Segundo uma pesquisa realizada em 2015, há atualmente no Brasil 141 hospitais que oferecem a oportunidade de crianças e jovens prosseguirem seus estudos. Essa pesquisa irá abordar 3 destes hospitais que possuem a classe hospitalar. Serão analisados os papéis do pedagogo e como esse processo foi e é inserido na realidade das crianças e adolescentes internadas. O estudo foi realizado dentro de uma abordagem qualitativa de caráter bibliográfico, e fundamentada por vários pesquisadores, enfatizando a importância da comunicação no processo de escolarização e como a rede de saúde, pode e deve acolher a escola nos seus espaços de internação, para que a criança e adolescente, se sinta mais acolhido, e sem a perda dos conhecimentos acadêmicos, e com isto, o hospital, se torna mais humanizado
Keywords: Educação; Hospitais; Escolarização; Criança; Adolescentes; Brasil